To compare the effectiveness of taping technique and hydrotherapy in treatment of primary dysmenorrhea - Arshad, Sonya; Qureshi, Muhammad Faisal; Deeba, Farah; Sarshad, Samreen; Shiraz, Sehrish; Farooq, Sidra; Abdul Majeed, Sidra; Ahmed , Sheeraz; Malik , Shafaq (International Journal of Endorsing Health Science Research, 2018)
Background: Dysmenorrhea is one of the common complaints in women. Globally, the reported prevalence rate is 90%. Sometimes the pain intensity is so severe that it may depict labour contractions. Hence, it greatly affects the productivity of women and causes socioeconomic lose. To subside such pain, over the counter medications are widely used, regardless of its systemic side effects. This study was conducted to estimate the extent to which women are affected with dysmenorrhea and to compare the effectiveness of Taping and Hydrotherapy for the treatment of primary dysmenorrhea. Methodology: A survey-based quasi experimental single blinded, two- stage study with pre-test and post-test design was conducted. Fifty menstruating women suffering from primary dysmenorrhea of grade 2 or 3 between the age group of 15 to 25 years were recruited and divided into two groups with 25 females in each group. Females with any severe co-morbidity, abdominal surgery within past 2 years, intrauterine contraceptive devices, any skin lesions (scar, cyst or erosions) or who have recently conceived were excluded from the study sample. Females in taping group received treatment 2 days prior to menstruation which then continued till the first day of cycle. The hydrotherapy group was treated with 30 minutes session for 2 days a week, during non-menstruating phase. Data was collected using a Menstrual Symptom Questionnaire (MSQ) and Verbal Multidimensional Scoring System (VMSS) to estimate the frequency of dysmenorrhea, specifically primary dysmenorrhea in our society. To assess the effectiveness of the intervention, Short-form McGill Pain Questionnaire (SF-MPQ) was completed before and after the intervention. The collected data was analyzed using SPSS ver. 22.0. Results: The survey revealed 92.4% of women were suffering from dysmenorrhea out of which 64% were primary dysmenorrheic. A significant decline was observed in Pain Rating Index (PRI) before and after intervention i.e. the mean PRI prior to the intervention was 29.53±2.53 for the taping group and 29.4±3.18 for the hydrotherapy group while after intervention it decreased up to 4.33±0.61 in taping and 4.26±0.7 in hydrotherapy group. Whereas, the Visual Analogue Scale (VAS) means before intervention were 8.53±1.06 and 8.73±1.03 for taping and hydrotherapy group respectively. Which then decreased to 3.93±1.03 and 5.2±1.52 for the two groups. The mean Present Pain Intensity (PPI) scores were 4.33±0.61 in taping and 4.26±0.7 in hydrotherapy group and reduced to 1.66±0.81 and 2.26±1.57. Conclusion: The study findings proclaimed that taping technique was found more effective in decreasing the painful cramps in women with primary dysmenorrhea as compared to the hydrotherapy.